Policymakers Priors and lnflation Density Forecasting - Vega, Marco (2004)
This paper models an inflation density forecast framework that closely resembles policymakers' actual behavior regarding the determination of the modal point, the uncertainty and asymmetry in inflation forecasts.The framework combines the prior information about these parameters available to policymakers with a standard parametric density estimation technique using Bayesian theory. The combination crucially hinges on an information-theoretic utility function gain for the policymaker from performing the forecast exercise.